Different combinations of CAD/CAM materials on the biomechanical behavior of a two-piece prosthetic solution - Mendes Tribst, Joao Paulo [UNESP]; Oliveira Dal Piva, Amanda Maria de [UNESP]; Souto Borges, Alexandre Luiz [UNESP]; Bottino, Marco Antonio [UNESP] (Quintessence Publishing Co Inc, 2019)
Aim: This study evaluated the stress distribution of implant-supported prostheses, varying the different combinations of computer-aided design/computer-aided manufacturing (CAD/CAM) materials between the hybrid abutment and the monolithic crown by three-dimensional (3D) finite element analysis (FEA). Materials and methods: Nine models were designed with Rhinoceros 3D and Ansys software. Each model contained a bone block of the molar area, including an implant (IH; empty set 3.75 x 11 mm) supporting a hybrid abutment (ceramic mesostructure (MS) cemented onto a titanium [Ti] base) and a monolithic crown. The occlusal load was applied to the fossa bottom (300 N; 30 degrees). The results were analyzed using the von Mises stress for each separated prosthetic structure and microstrain for the bone tissue. Result: Von Mises maps of the crown, ceramic MS, implant, screw, and cement layers showed a decreased stress concentration as the elastic modulus (E modulus) of the ceramic crown (CR) associated with a rigid ceramic MS decreased. No differences in bone tissue regarding microstrain were observed. Conclusion: Implant-supported crowns present less stress concentration when a rigid abutment is associated with resilient crowns.
Keywords: ceramics; finite element analysis (FEA); dental implants; material testing; dental implant-abutment design; dental materials